2014
DOI: 10.1097/prs.0000000000000225
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Correction of Pierre Robin Sequence

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Early studies of MDO in young children reported high rates of clinical resolution of symptoms 40 and subsequent studies involving PSG have shown substantial improvement in OSAS in the majority of patients. 41 MDO has been shown to increase not only the length of the mandible ramus and body but also the airway volume in the hypopharynx. 14 Still, there are no large prospective studies of MDO in children with micrognathia.…”
Section: Therapies For Osas In the Paediatric Craniofacial Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies of MDO in young children reported high rates of clinical resolution of symptoms 40 and subsequent studies involving PSG have shown substantial improvement in OSAS in the majority of patients. 41 MDO has been shown to increase not only the length of the mandible ramus and body but also the airway volume in the hypopharynx. 14 Still, there are no large prospective studies of MDO in children with micrognathia.…”
Section: Therapies For Osas In the Paediatric Craniofacial Populationmentioning
confidence: 99%
“…Although no large prospective studies have been performed, available data suggests that tongue-lip adhesion results in a shorter hospital stay but MDO results in improved OSAS and earlier return to oral feeding 43 , at least in non-syndromic infants with micrognathia. Infants undergoing MDO may be less likely to require a second surgery to correct persistent upper airway obstruction 41 .…”
Section: Therapies For Osas In the Paediatric Craniofacial Populationmentioning
confidence: 99%
“…Flores et al compared MDO versus TLA (107). They found that patients undergoing MDO demonstrated significantly higher oxygen saturation levels and lower AHI at 1 month and 1 year postoperatively compared with TLA (despite the MDO group showing evidence of more severe airway obstruction pre-procedure).…”
Section: Treatment Of Osa In Children With Pierre Robin Sequencementioning
confidence: 99%
“…A meta-analysis found that 84% of children who were tracheostomy dependent were able to be decannulated following MDO [42]. Early studies of MDO in infants reported high rates of clinical resolution of symptoms [42] and subsequent studies involving polysomnography have shown significant improvement in OSA in the majority of patients [43]. There have been no large prospective studies of MDO in children with micrognathia.…”
Section: Management Of Upper Airway Obstructionmentioning
confidence: 99%
“…Recent studies comparing surgical outcomes of TLA with MDO suggest that TLA results in a shorter hospital stay but that MDO is better at treating OSA and earlier return to oral feeding [46], at least in non-syndromic infants with micrognathia. Infants undergoing MDO may be less likely to require a second surgery to correct persistent upper airway obstruction [43]. …”
Section: Management Of Upper Airway Obstructionmentioning
confidence: 99%